Prototipe Penentu Kadar Karet Kering (K3) Lateks (Hevea Brasiliensis) Menggunakan Metode Kapasitif Berbasis Mikrokontroler ATMega8535 - Ade Agung Harnawan; Mawar Resty Anggraini; Iwan Sugriwan (Jurnal Fisika FLUX, 2019)
The latex K3 determinant prototype using the ATMEGA8535 microcontroller based capacitive method was completed . K3 measuring system is arranged in several systems, there are parallel plate capacitive sensors, multivibrator, frequency to voltage converter, non inverting amplifier, ATMega8535 microcontroller module and 16x2 character LCD. The value of the latex capacitance is converted into a frequency by a multivibrator, then the frequency is converted to voltage and connected to the microcontroller to be processed and displayed the K3 value of latex on the LCD. The voltage characterization processes with a K3 value produces a K3 characteristic equation = - 19.996v + 54,831. These equations are processed in the BASCOM AVR program which is embedded in the microcontroller. The determination of K3 is used capacitive sensor which functions to read changes in the dielectric constant of latex , which has dimensions of 2.5 x 2.5cm with a distance between pieces of 0.6cm. In testing, the prototype can determine the value of K3 from 18% to 28% and the difference in K3 values from 0.3% to 1.2% compared to industrial measurements.